NdFeB base material preparation method capable of improving diffusion depth
Through the use of hydrogen crushing treatment and transition metal powder hybrid technology in the preparation of 材 iron boron substrate, combined with high -strength magnetic field molding and vacuum sintering treatment, the problem of insufficient diffusion and magnetic instability in existing technologies has been solved. Crystal diffusion and magnetic performance improvement.
Patent Information
- Application Number
- CN202411596547.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-01-24
AI Technical Summary
The existing diffusion source containing heavy rare earth alloys has a high melting point and poor wetting, which limits the diffusion depth. The diffusion source of light rare earth alloys has a much lower lift effect than that of heavy rare earth alloys, resulting in the diffusion depth of the substrate being unsatisfied and after sintering. The consistency and stability of magnetic properties are poor.
The NdFeB alloy flakes are subjected to hydrogen crushing treatment, mixed with transition metal powder in a specific ratio, and pulverized in a jet mill, then molded in a high-intensity magnetic field, followed by vacuum sintering and aging treatment, and finally crystallization. Boundary diffusion processing.
It improves the deepening of the crystal boundary, improves the consistency and stability of the magneticity after sintering, enhances the strength of magnetic saturation, and meets the high thickness of the crystal diffusion needs.
Smart Images

Figure CN119361313A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of NdFeB grain boundary diffusion technology, in particular to a method for preparing a NdFeB substrate with improved diffusion depth. Background Art
[0002] At present, the grain boundary diffusion process is an important means to reduce the amount of heavy rare earths. There are also many other methods of grain boundary diffusion, such as magnetron sputtering, evaporation, surface coating, screen printing, electrophoretic deposition, etc. Because new energy and white household appliances are the most widely used, surface coating and screen printing are currently the most popular.
[0003] Research in recent years has shown that grain boundary diffusion can not only introduce heavy rare earth elements such as Dy and Tb to increase the anisotropy field on the surface of the main phase grains, but also introduce light rare earth elements such as praseodymium and neodymium, and even add non-rare earth elements such as copper, aluminum, and gallium to regulate the grain boundary phase in order to achieve the purpose of increasing the coercivity.
[0004] Existing alloy diffusion sources containing heavy rare earths generally have a high melting point and poor wettability, and are easily accumulated in the variable layer, which limits the diffusion depth. The enhancement effect of light rare earth alloy diffusion sources is far lower than that of heavy rare earth alloy diffusion sources. Therefore, problems such as insufficient diffusion depth of the substrate and poor consistency and stability of magnetism after sintering arise. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a NdFeB substrate with improved diffusion depth, which solves the problem that the existing alloy diffusion sources containing heavy rare earths generally have a high melting point, poor wettability, and are easily accumulated in the variable layer, which limits the diffusion depth. The improvement effect of the light rare earth alloy diffusion source is far lower than that of the heavy rare earth alloy diffusion source, thus resulting in insufficient diffusion depth of the substrate and poor consistency and stability of the magnetism after sintering.
[0006] To achieve the above objectives, the present invention is implemented by the following technical scheme: A method for preparing a NdFeB substrate with improved diffusion depth, comprising the following steps:
[0007] S1. Crushing: subjecting the NdFeB alloy sheet to hydrogen crushing treatment;
[0008] S2, mixing: mixing the hydrogen-decomposed coarse powder with the transition metal powder in a mass ratio of (98-99.5): (0.5-2);
[0009] S3, grinding: adding the mixture to the organic compound and then grinding in a jet mill;
[0010] S4, molding: the fine powder after powdering is oriented and molded in a molding chamber with a magnetic field of more than 1.6T;
[0011] S5, sintering: vacuum sintering the green billet to obtain a NdFeB blank;
[0012] S6, shape processing: Process the blank into square pieces with the same length and width but different thickness after processing;
[0013] S7, cleaning, diffusion and aging treatment: after degreasing, cleaning and drying, the square pieces of different thicknesses are subjected to grain boundary diffusion and aging treatment;
[0014] S8. Testing: Use permanent magnetic performance tester to carry out performance tests.
[0015] Preferably, the hydrogen content of the alloy after hydrogen crushing treatment in step S1 is 700-1200 ppm.
[0016] Preferably, the transition metal powder in step S2 is one or more of the first transition series in the d-block, and the average particle size of the powder is 20-100 μm.
[0017] Preferably, the mixing time in step S3 is 2-5 hours, the proportion of organic compound added is 0.1%, the average particle size after airflow milling is 2.5-4 μm, and the mixture is stored in nitrogen.
[0018] Preferably, the orientation molding in step S4 requires a magnetic field strength of >1.6T and an oxygen content in the molding chamber of <300ppm.
[0019] Preferably, the vacuum sintering temperature in step S5 is 1020-1100° C., the holding time is 4-10 h, and the vacuum degree is <0.5 Pa.
[0020] Preferably, the square sheet in step S6 is a substrate with a length and width of 30 mm and a thickness of 3 mm, 5 mm, 8 mm, and 10 mm respectively.
[0021] Preferably, the surface pH value after degreasing, cleaning and drying in step S7 is 6-8, the diffusion source heavy rare earth for grain boundary diffusion mainly includes one or more of Dy alloy, Tb alloy, dysprosium hydride, terbium hydride, dysprosium oxide and terbium oxide, the grain boundary diffusion method is mainly any one of PVD, coating and screen printing, the diffusion treatment temperature is 850-930°C, the diffusion time is 12-30h, the aging treatment temperature is 450-530°C, the aging time is 3-10h, and the vacuum degree is <0.5Pa.
[0022] Preferably, the performance test in step S8 is performed using a NI M-62000 permanent magnetic performance tester, and the coils are in the same group.
[0023] The present invention provides a method for preparing a NdFeB substrate with improved diffusion depth. The method has the following beneficial effects:
[0024] In the present invention, a heavy rare earth-free NdFeB alloy powder and a transition metal powder mixing technology are used to strengthen the grain boundaries, improve the continuity of the flow between the grain boundaries during grain boundary diffusion, and form a continuous grain boundary phase, so as to meet the high thickness of the grain boundary diffusion depth. Since the complex formed by the transition metal is paramagnetic, the magnetization saturation intensity can be improved after addition, thereby improving the existing heavy rare earth-containing alloy diffusion source. Generally, the melting point is high, the wettability is poor, and it is easy to accumulate in the variable layer, which limits the diffusion depth. The improvement effect of the light rare earth alloy diffusion source is much lower than that of the heavy rare earth alloy diffusion source, so there are problems such as the diffusion depth of the substrate is not satisfied and the consistency and stability of the magnetism after sintering are poor. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a flow chart of the manufacturing process of the present invention;
[0026] Figure 2 It is a comparison diagram of the magnetization characteristics of the present invention. DETAILED DESCRIPTION
[0027] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The following is further introduced in conjunction with specific embodiments:
[0029] Embodiment 1:
[0030] A method for preparing a NdFeB substrate with improved diffusion depth comprises the following steps:
[0031] S1: Smelting: Using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of Pr7.8Nd23.2B0.93Cu0.15Co0.5Zr0.15Nb0.3Ga0.1, Fe balance, a vacuum melting furnace is used to make alloy sheets with a thickness of 0.2-0.5mm.
[0032] S2: Hydrogen cracking: The above alloy sheet is subjected to hydrogen cracking treatment to obtain a coarse powder after hydrogen cracking, with a hydrogen content of about 700-1200ppm and a thickness of about 10-100μm.
[0033] S3: Powder mixing: The above coarse powder and a transition metal powder are mixed at a ratio of 0.5%, and 0.1% of an organic additive is added and mixed thoroughly.
[0034] S4: Jet mill: Grind the coarse powder after mixing by jet mill, add a certain proportion of antioxidant to the fine powder after grinding, and stir it fully by three-dimensional or high-speed mixer in a nitrogen environment with a purity of 99.99%.
[0035] S5: Molding: Orientation molding is carried out under the condition that the orientation magnetic field strength is greater than 1.6T and the oxygen content of the press is less than 300ppm, followed by vacuum packaging and cold isostatic pressing to achieve a densification effect.
[0036] S6: Sintering: Place the green body after isostatic pressing in a vacuum sintering furnace, evacuate to less than 0.5Pa, perform gradient sintering, and then perform aging treatment. The sintering temperature is 1070℃, the sintering time is 6h, the aging temperature is 480℃, and the aging time is 5h.
[0037] S7: The sintered blank after aging is processed into a D10*10 standard sample injection and tested using a NI M-62000 permanent magnetic properties tester.
[0038] Comparative Example:
[0039] S1: Smelting: Using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of Pr7.8Nd23.2B0.93Cu0.15Co0.5Zr0.15Nb0.3Ga0.1, Fe balance, a vacuum melting furnace is used to make alloy sheets with a thickness of 0.2-0.5mm.
[0040] S2: Hydrogen cracking: The above alloy sheet is subjected to hydrogen cracking treatment to obtain a coarse powder after hydrogen cracking, with a hydrogen content of about 700-1200ppm and a thickness of about 10-100μm.
[0041] S3: Mixing powder: Add 0.1% of organic additives to the above coarse powder and mix thoroughly.
[0042] S4: Jet mill: Grind the coarse powder after mixing by jet mill, add a certain proportion of antioxidant to the fine powder after grinding, and stir it fully by three-dimensional or high-speed mixer in a nitrogen environment with a purity of 99.99%.
[0043] S5: Molding: Orientation molding is carried out under the condition that the orientation magnetic field strength is greater than 1.6T and the oxygen content of the press is less than 300ppm, followed by vacuum packaging and cold isostatic pressing to achieve a densification effect.
[0044] S6: Sintering: Place the green body after isostatic pressing in a vacuum sintering furnace, evacuate to less than 0.5Pa, perform gradient sintering, and then perform aging treatment. The sintering temperature is 1070℃, the sintering time is 6h, the aging temperature is 480℃, and the aging time is 5h.
[0045] S7: The sintered blank after aging is processed into a D10*10 standard sample injection and tested using a NI M-62000 permanent magnetic properties tester.
[0046] Embodiment 2:
[0047] S1: Smelting: Using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of Pr7.8Nd23.2B0.93Cu0.15Co0.5Zr0.15Nb0.3Ga0.1, Fe balance, a vacuum melting furnace is used to make alloy sheets with a thickness of 0.2-0.5mm.
[0048] S2: Hydrogen cracking: The above alloy sheet is subjected to hydrogen cracking treatment to obtain a coarse powder after hydrogen cracking, with a hydrogen content of about 700-1200ppm and a thickness of about 10-100μm.
[0049] S3: Powder mixing: The above coarse powder and a transition metal powder are mixed at a ratio of 0.8%, and 0.1% of an organic additive is added and mixed thoroughly.
[0050] S4: Jet mill: Grind the coarse powder after mixing by jet mill, add a certain proportion of antioxidant to the fine powder after grinding, and stir it fully by three-dimensional or high-speed mixer in a nitrogen environment with a purity of 99.99%.
[0051] S5: Molding: Orientation molding is carried out under the condition that the orientation magnetic field strength is greater than 1.6T and the oxygen content of the press is less than 300ppm, followed by vacuum packaging and cold isostatic pressing to achieve a densification effect.
[0052] S6: Sintering: Place the green body after isostatic pressing in a vacuum sintering furnace, evacuate to less than 0.5Pa, perform gradient sintering, and then perform aging treatment. The sintering temperature is 1070℃, the sintering time is 6h, the aging temperature is 480℃, and the aging time is 5h.
[0053] S7: The sintered blank after aging is processed into a D10*10 standard sample injection and tested using a NI M-62000 permanent magnetic properties tester.
[0054] Embodiment 3:
[0055] S1: Smelting: Using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of Pr7.8Nd23.2B0.93Cu0.15Co0.5Zr0.15Nb0.3Ga0.1, Fe balance, a vacuum melting furnace is used to make alloy sheets with a thickness of 0.2-0.5mm.
[0056] S2: Hydrogen cracking: The above alloy sheet is subjected to hydrogen cracking treatment to obtain a coarse powder after hydrogen cracking, with a hydrogen content of about 700-1200ppm and a thickness of about 10-100μm.
[0057] S3: Powder mixing: The above coarse powder and a transition metal powder are mixed at a ratio of 1%, and 0.1% of an organic additive is added and mixed thoroughly.
[0058] S4: Jet mill: Grind the coarse powder after mixing by jet mill, add a certain proportion of antioxidant to the fine powder after grinding, and stir it fully by three-dimensional or high-speed mixer in a nitrogen environment with a purity of 99.99%.
[0059] S5: Molding: Orientation molding is carried out under the condition that the orientation magnetic field strength is greater than 1.6T and the oxygen content of the press is less than 300ppm, followed by vacuum packaging and cold isostatic pressing to achieve a densification effect.
[0060] S6: Sintering: Place the green body after isostatic pressing in a vacuum sintering furnace, evacuate to less than 0.5Pa, perform gradient sintering, and then perform aging treatment. The sintering temperature is 1070℃, the sintering time is 6h, the aging temperature is 480℃, and the aging time is 5h.
[0061] S7: The sintered blank after aging is processed into a D10*10 standard sample injection and tested using a NI M-62000 permanent magnetic properties tester.
[0062] Embodiment 4:
[0063] S1: Smelting: Using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of Pr7.8Nd23.2B0.93Cu0.15Co0.5Zr0.15Nb0.3Ga0.1, Fe balance, a vacuum melting furnace is used to make alloy sheets with a thickness of 0.2-0.5mm.
[0064] S2: Hydrogen cracking: The above alloy sheet is subjected to hydrogen cracking treatment to obtain a coarse powder after hydrogen cracking, with a hydrogen content of about 700-1200ppm and a thickness of about 10-100μm.
[0065] S3: Powder mixing: The above coarse powder and a transition metal powder are mixed at a ratio of 1.2%, and 0.1% of an organic additive is added and mixed thoroughly.
[0066] S4: Jet mill: Grind the coarse powder after mixing by jet mill, add a certain proportion of antioxidant to the fine powder after grinding, and stir it fully by three-dimensional or high-speed mixer in a nitrogen environment with a purity of 99.99%.
[0067] S5: Molding: Orientation molding is carried out under the condition that the orientation magnetic field strength is greater than 1.6T and the oxygen content of the press is less than 300ppm, followed by vacuum packaging and cold isostatic pressing to achieve a densification effect.
[0068] S6: Sintering: Place the green body after isostatic pressing in a vacuum sintering furnace, evacuate to less than 0.5Pa, perform gradient sintering, and then perform aging treatment. The sintering temperature is 1070℃, the sintering time is 6h, the aging temperature is 480℃, and the aging time is 5h.
[0069] S7: The sintered blank after aging is processed into a D10*10 standard sample injection and tested using a NI M-62000 permanent magnetic properties tester.
[0070] Embodiment 5:
[0071] S1: Smelting: Using metal praseodymium, neodymium, ferroboron, copper, cobalt, ferroniobium, gallium, zirconium and pure iron as raw materials, according to the composition design of Pr7.8Nd23.2B0.93Cu0.15Co0.5Zr0.15Nb0.3Ga0.1, Fe balance, a vacuum melting furnace is used to make alloy sheets with a thickness of 0.2-0.5mm.
[0072] S2: Hydrogen cracking: The above alloy sheet is subjected to hydrogen cracking treatment to obtain a coarse powder after hydrogen cracking, with a hydrogen content of about 700-1200ppm and a thickness of about 10-100μm.
[0073] S3: Powder mixing: The above coarse powder and a transition metal powder are mixed at a ratio of 0.5%, and 0.1% of an organic additive is added and mixed thoroughly.
[0074] S4: Jet mill: Grind the coarse powder after mixing by jet mill, add a certain proportion of antioxidant to the fine powder after grinding, and stir it fully by three-dimensional or high-speed mixer in a nitrogen environment with a purity of 99.99%.
[0075] S5: Molding: Orientation molding is carried out under the condition that the orientation magnetic field strength is greater than 1.6T and the oxygen content of the press is less than 300ppm, followed by vacuum packaging and cold isostatic pressing to achieve a densification effect.
[0076] S6: Sintering: Place the green body after isostatic pressing in a vacuum sintering furnace, evacuate to less than 0.5Pa, perform gradient sintering, and then perform aging treatment. The sintering temperature is 1070℃, the sintering time is 6h, the aging temperature is 480℃, and the aging time is 5h.
[0077] S7: The sintered blank after aging is processed into a D10*10 standard sample injection and tested using a NI M-62000 permanent magnetic properties tester.
[0078] The performance results are shown in Table (1)
[0079]
[0080] Table (1)
[0081] From the above examples, it can be seen that after adding transition metal powder to the coarse powder, the coercivity of the magnet can be slightly increased, but the remanence will be reduced to a certain extent, especially when the addition ratio is above 1%. As can be seen from Example 1, adding 0.5% transition metal powder can achieve a balance. If the amount of transition metal powder added is too much, the effect of improving the intrinsic coercivity is not obvious, so Example 1 is the best.
[0082] The transition metal is one or more elements in the first transition series, that is, it can be one or more elements in the d-zone first transition series such as Cu, Zn or V, Cr, Ti, Co, etc.
[0083] The sintered blanks in Example 1 and the comparative example were respectively made into square pieces with a length and width of 30 mm and a thickness of 3 mm, 5 mm, 8 mm, and 10 mm;
[0084] The thickness direction is the magnetization direction. After degreasing, cleaning, drying and other surface treatments, a raw material mainly composed of terbium hydride is evenly sprayed on the magnetized surface. The weight gain after coating is 0.55% Tb. After high-temperature tunnel drying, the material is packed in a box for vacuum sintering. Diffusion sintering is performed at a temperature of 850°C-920°C, preferably 870°C. After keeping the temperature for 15 hours, it is cooled to 50°C and then subjected to aging treatment. The temperature is preferably 480°C. After keeping the temperature for 6 hours, it is cooled to 40°C and then taken out of the furnace.
[0085] The square pieces after grain boundary diffusion treatment were tested using NI M-62000 permanent magnetic properties tester, and the results are shown in Table (2)
[0086] Table (2)
[0087]
[0088] It can be seen from Table 2 that the Hcj increment after diffusion decreases with the increase of product thickness, but under the condition of the same thickness, the Hcj increment of Example 1 is higher than that of the comparative example, which indicates that the addition of transition metal powder in the invention helps to lower its melting point, improve the wettability between grain boundaries, strengthen the flow continuity between grain boundaries, and further enhance the diffusion depth of the grain boundary diffusion process, thereby improving the demagnetization resistance of the sintered permanent magnet.
[0089] The sintered blanks in Example 1 and the comparative example were prepared into samples with the size of
[0090] 8 square pieces of 39*10.7*1.9mm, of which 1.9mm is the thickness in the magnetization direction. A magnetization device with a magnetic field peak of 3T was selected, and 2 pieces were magnetized at 2000V, 2200V, and 2400V respectively. In addition, 2 pieces were magnetized at 3500V as saturation magnetization. The above samples were tested for magnetic flux and saturation was calculated, and the results are shown in Table (3).
[0091] Table (3)
[0092]
[0093] It can be seen from Table (3) that the magnetization saturation rate in Example 1 is 89.62%-99.01%, and the magnetization saturation rate in the comparative example is 86.74%-97.22%. It can also be seen from the average magnetization saturation rate that the magnetization saturation rate of the NdFeB substrate with 0.5% transition metal powder added is high regardless of low voltage or high voltage.
[0094] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a NdFeB substrate with improved diffusion depth, characterized in that: The following steps are involved: S1. Crushing: subjecting the NdFeB alloy sheet to hydrogen crushing treatment; S2, mixing: mixing the hydrogen-decomposed coarse powder with the transition metal powder in a mass ratio of (98-99.5): (0.5-2); S3, grinding: adding the mixture to the organic compound and then grinding in a jet mill; S4, molding: the fine powder after powdering is oriented and molded in a molding chamber with a magnetic field of more than 1.6T; S5, sintering: vacuum sintering the green billet to obtain a NdFeB blank; S6, shape processing: Process the blank into square pieces with the same length and width but different thickness after processing; S7, cleaning, diffusion and aging treatment: after degreasing, cleaning and drying, the square pieces of different thicknesses are subjected to grain boundary diffusion and aging treatment; S8. Testing: Use permanent magnetic performance tester to carry out performance tests.
2. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 1, characterized in that: The hydrogen content of the alloy after hydrogen crushing in step S1 is 700-1200 ppm.
3. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 1, characterized in that: The transition metal powder in step S2 is one or more of the first transition series in the d-block, and the average particle size of the powder is 20-100 μm.
4. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 1, characterized in that: The mixing time in step S3 is 2-5 hours, the addition ratio of the organic compound is 0.1%, the average particle size after airflow grinding is 2.5-4 μm, and the powder is stored in nitrogen.
5. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 1, characterized in that: The orientation molding in step S4 requires that the magnetic field strength is greater than 1.6 T and the oxygen content in the molding chamber is less than 300 ppm.
6. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 5, characterized in that: The vacuum sintering temperature in step S5 is 1020-1100° C., the holding time is 4-10 hours, and the vacuum degree is less than 0.5 Pa.
7. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 1, characterized in that: The square sheet in step S6 is a substrate with a length and width of 30 mm and thicknesses of 3 mm, 5 mm, 8 mm, and 10 mm, respectively.
8. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 1, characterized in that: The pH value of the surface after degreasing, cleaning and drying in step S7 is 6-8, the heavy rare earth diffusion source for grain boundary diffusion mainly includes one or more of Dy alloy, Tb alloy, dysprosium hydride, terbium hydride, dysprosium oxide and terbium oxide, the grain boundary diffusion method is mainly any one of PVD, coating and screen printing, the diffusion treatment temperature is 850-930°C, the diffusion time is 12-30h, the aging treatment temperature is 450-530°C, the aging time is 3-10h, and the vacuum degree is <0.5Pa.
9. The method for preparing a NdFeB substrate with improved diffusion depth according to claim 1, characterized in that: The performance test in step S8 adopts a NIM-62000 permanent magnetic performance tester, and the coils are in the same group.
Citation Information
Cited By
Neodymium-iron-boron magnet and preparation method thereof
CN121439430A